Artificial human telomeres from DNA nanocircle templates - Lindström, Ulf M. (National Academy of Sciences, 2002)
Human telomerase is a reverse-transcriptase enzyme that synthesizes the multikilobase repeating hexamer telomere sequence (TTAGGG)(n) at the ends of chromosomes. Here we describe a designed approach to mimicry of telomerase, in which synthetic DNA nanocircles act as essentially infinite catalytic templates for efficient synthesis of long telomeres by DNA polymerase enzymes. Results show that the combination of a nanocircle and a DNA polymerase gives a positive telomere-repeat amplification protocol assay result for telomerase activity, and similar to the natural enzyme, it is inhibited by a known telomerase inhibitor. We show that artificial telomeres can be engineered on human chromosomes by this approach. This strategy allows for the preparation of synthetic telomeres for biological and structural study of telomeres and proteins that interact with them, and it raises the possibility of telomere engineering in cells without expression of telomerase itself. Finally, the results provide direct physical support for a recently proposed rolling-circle mechanism for telomerase-independent telomere elongation.